Hidden and apparent twins in uranyl‐oxide minerals agrinierite and rameauite: a demonstration of metric and reticular merohedry. Issue 6 (2nd November 2021) - Plášil, Jakub; Petříček, Václav; Škoda, Radek; Meisser, Nicolas; Kasatkin, Anatoly V.
Abstract : Two examples of twinning, by metric and reticular merohedry, in uranyl‐oxide minerals demonstrate the care that must be taken during structural studies, and not only of such complex materials. This contribution also demonstrates the possibilities of the Jana2020 program in revealing twinning and in subsequent refinement. Abstract : In this work, the structures of chemically related uranyl‐oxide minerals agrinierite and rameauite have been revisited and some corrections to the available structure data are provided. Both structures were found to be twinned. The two minerals are chemically similar, and though their structures differ considerably, their unit‐cell metrics are similar. Agrinierite was found to be twinned by metric merohedry (diffraction type I), whereas the structure of rameauite is twinned by reticular merohedry (diffraction type II). The twinning of the monoclinic unit cells (true cells) leads to pseudo‐orthorhombic or pseudo‐tetragonal supercells in the single‐crystal diffraction patterns of both minerals. According to the new data and refinement, agrinierite is monoclinic (space group Cm ), with a = 14.069 (3), b = 14.220 (3), c = 13.967 (3) Å, β = 120.24 (12)° and V = 2414.2 (12) Å 3 ( Z = 2). The twinning can be expressed as a mirror in (101) (apart from the inversion twin), which leads to a supercell with a = 14.121, b = 14.276, c = 24.221 Å and V = 2 × 2441 Å 3, which is F centered. The new structure refinement converged to R = 3.54% for 6545 unique observed reflections with I > 3σ( I ) and GOF = 1.07. Rameauite is also monoclinic (space group Cc ), with a = 13.947 (3), b = 14.300 (3), c = 13.888 (3) Å, β = 118.50 (3)° and V = 2434.3 (11) Å 3 ( Z = 2). The twinning can be expressed as a mirror in (1 01) (apart from the inversion twin), which leads to a supercell with a = 14.223, b = 14.300, c = 23.921 Å and V = 2 × 2434 Å 3, which is C centered. The new structure refinement of rameauite converged to R = 4.23% for 2344 unique observed reflections with I > 3σ( I ) and GOF = 1.48. The current investigation documented how peculiar twinning can be, not only for this group of minerals, and how care must be taken in handling the data biased by twinning.